Constitutional Statutes. (24th December 2016) - Ahmed, Farrah; Perry, Adam
Abstract: In recent years, British courts have treated constitutional statutes differently from ordinary statutes. This article sets outs to explain: (i) how courts have treated constitutional statutes differently from ordinary statutes; (ii) what a constitutional statute is; and (iii) why constitutional statutes should be treated differently from ordinary statutes. Courts have made it harder for ordinary statutes to repeal constitutional statutes by implication, and easier for constitutional statutes to repeal ordinary statutes by implication. A constitutional statute is a statute which regulates state institutions, and which possesses importance of a particular type that we describe. The nature of a constitutional statute largely—but not entirely—justifies the special treatment they have been given. These conclusions have wider implications, including for proposals to codify the British constitution.